Clozapine administration in clinical practice: once‐daily versus divided dosing. (16th May 2016) - Takeuchi, H.; Powell, V.; Geisler, S.; DeSanti, M.; Fervaha, G.; Agid, O.; Kane, J. M.; Remington, G.
Abstract : Objective: While it is recommended that clozapine be administered in a divided dosing regimen, it is unclear whether this recommendation is followed in real‐world clinical practice. In two large datasets, we examined clozapine dosing frequency and patient characteristics across different dosing regimens. Method: We conducted a cross‐sectional survey, collecting data on patients receiving clozapine in August/September 2015 from the Centre for Addiction and Mental Health (CAMH) in Toronto, Canada, and The Zucker Hillside Hospital (ZHH) in New York, United States. Results: Of 676 and 308 patients included in CAMH and ZHH datasets, clozapine was prescribed once daily in 75.1% and 74.4%, even though doses exceeding 200 mg/day were administered in 88.6% and 84.4% of the respective samples. No significant difference was found in the rates of positive symptom remission between once‐daily vs. divided dosing (79.7% vs. 80.5%, P = 1.00). Higher clozapine dose and use of anticholinergic medications were significantly associated with divided dosing in both datasets. Older age or male gender was related to divided dosing in CAMH or ZHH dataset respectively. Conclusion: Despite the product monograph recommendation, clozapine is frequently prescribed once daily in North America. Further studies are needed to compare clinical outcomes between once‐daily vs. divided clozapine dosing.